2014
DOI: 10.1590/s0103-05822014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Assistance to children in palliative care in the Brazilian scientific literature

Abstract: Objective: To describe what has been published in Brazilian scientific literature regarding pediatric palliative care. Data sources: Bibliographic review with a descriptive approach. In LILACS and SciELO databases, the descriptors "palliative care", "child", "pediatrics", "terminal illness" and "death" were sought, from January 2002 to December 2011. The eight selected articles were analyzed according to year of publication, type of study, data collected, target population, pathology, professionals involved, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Therapeutic limitation for children: a systematic review on end-of-life education are of paramount importance for health professionals, because it was also found that they struggle with issues related to the care of the family, of the child and of themselves, because there is too much physical and psychological wear and tear 38 .…”
Section: Care In the Death And Dying Process Of A Child Patientmentioning
confidence: 99%
“…Therapeutic limitation for children: a systematic review on end-of-life education are of paramount importance for health professionals, because it was also found that they struggle with issues related to the care of the family, of the child and of themselves, because there is too much physical and psychological wear and tear 38 .…”
Section: Care In the Death And Dying Process Of A Child Patientmentioning
confidence: 99%
“…Es esencial, ante la complejidad de los cuidados al final de la vida, que se aborden los cuidados paliativos en oncología pediátrica durante los estudios de grado de los profesionales sanitarios, además de analizar todas las cuestiones éticas y humanas involucradas en ese proceso 37 . Por lo tanto, la capacitación y formación continua son de extrema importancia para estos profesionales, ya que también se constató la dificultad que tenían en tratar asuntos relacionados con la atención a la familia, el menor y de sí mismos, debido al excesivo desgaste físico y psíquico 38 .…”
Section: Cuidados Durante El Proceso De Morir Y Muerte En Pacientes P...unclassified
“…Assim, capacitação e educação continuada são de suma importância para profissionais da área da saúde. Pois também se constatou sua dificuldade em lidar com questões relacionadas ao cuidado com a família, com a criança e consigo mesmo, por haver demasiado desgaste físico e psicológico 38 .…”
Section: Cuidado No Processo De Morte E O Morrer De Paciente Infantilunclassified